Vacancy type ZIF-8 pseudocapacitance material and preparation method and application thereof
By generating and air-pyrolyzing zeolite imidazolate framework material-8 in an alcohol solvent and using pulsed potential activation to etch Zn2+ ions, a vacancy-type ZIF-8 pseudocapacitive material was prepared, which solved the problem of complex and high-cost etching in the existing technology and improved the charge storage performance of the supercapacitor.
Patent Information
- Application Number
- CN202511163676.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-08-20
- Publication Date
- 2025-10-03
- Estimated Expiration
- 2045-08-20
AI Technical Summary
In the prior art, the etching method of zeolite imidazolate framework material-8 is complex and costly, which limits its wide application in supercapacitors and lacks an efficient and low-cost etching method.
Zeolite imidazolate framework material-8 is generated by reacting zinc source and imidazole organic ligand in alcohol organic solvent, and defective zeolite imidazolate framework material-8 is formed by air pyrolysis. Zn2+ ions are etched in potassium hydroxide solution using pulse potential activation to form vacancy-type ZIF-8 pseudocapacitive material.
The specific capacitance performance of ZIF-8 pseudocapacitive materials is improved, the electron transfer efficiency and Faradaic reaction ability are enhanced, and it has excellent energy density and power density, making it suitable for large-scale production.
Smart Images

Figure CN120748936A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of supercapacitor materials, and more particularly to a vacancy-type ZIF-8 pseudocapacitor material, a preparation method, and an application thereof. Background Art
[0002] Supercapacitors are a new type of energy storage component in the energy industry, playing a strategic role in the energy revolution. Supercapacitors are capable of rapid energy regulation. Compared to the minute-level dispatch response of lithium batteries, their millisecond-level response has a very high success rate in regulating instantaneous fluctuations in the power grid. Supercapacitors also have an exceptionally long cycle life, typically reaching 100,000 cycles, which can save up to ten years of maintenance costs for large-scale IoT devices, resulting in extremely high economic benefits. Furthermore, the dual-track power-energy collaboration formed by supercapacitors and energy devices such as lithium batteries is building a more powerful and complete energy ecosystem, which will play a vital role in key areas such as smart grids, new energy vehicles, and aerospace.
[0003] Unlike traditional capacitors, supercapacitors have a separate charge layer at the interface between the positive and negative electrodes and the electrolyte, so supercapacitors are also called double-layer capacitors. Relying on this charge layer, charges are stored and released in between, and no Faradaic reaction is involved. During the charging process, the positive and negative charges in the double layer attract each other, and the electrolyte ions on the electrodes cannot migrate into the electrolyte, so a stable potential difference between the positive and negative electrodes can be maintained to achieve energy storage. During the discharge process, the electrons on the negative electrode are transferred to the positive electrode through the load, the double layer balance between the positive and negative electrodes is broken, and the electrolyte ions return to the electrolyte to complete the charge release. Pseudocapacitors usually use transition metal oxides, hydroxides, sulfides, etc. to undergo Faradaic reactions to improve the charge storage capacity. Zeolite imidazolate framework material-8, as a metal-organic framework material, has a wide range of applications in supercapacitors due to its high specific surface area and small pore size. Its specific surface area can be as high as 1300m 2 / g~1600m 2 / g, and the pore size can be ≤2nm. The specific capacitance of pure zeolite imidazolate framework material is only in the order of tens of F / g, which can be improved after calcination in air, but is also below 200F / g. Etching is a commonly used treatment method, which can enlarge the pore size to expand the ion transmission channel and expose more active sites to improve the conductivity and energy storage capacity of the material. Common etching methods include acid etching, alkaline etching, template etching, plasma etching, etc., but they have the disadvantages of complex process, long reaction time and high cost, which limit their wide application. There is a lack of an efficient, low-cost, simple and easy etching method. Summary of the Invention
[0004] In response to the above problems, the present invention provides a vacancy-type ZIF-8 pseudocapacitive material, a preparation method, and an application. The vacancy-type ZIF-8 pseudocapacitive material prepared according to the method of the present invention has a high specific capacitance and excellent energy density and power density.
[0005] The first object of the present invention is to provide a method for preparing a vacancy-type ZIF-8 pseudocapacitive material, comprising the following steps: A zinc source and an imidazole organic ligand are added to an alcohol organic solvent to cause a coordination reaction. During the reaction, nitrogen in the imidazole organic ligand coordinates with zinc ions in the zinc source to obtain a zeolite imidazole ester framework material-8.
[0006] The zeolite imidazolate framework material-8 is thermally decomposed in an air atmosphere to obtain the defective zeolite imidazolate framework material-8.
[0007] Defective zeolite imidazolate framework material-8, acetylene black, a binder and a solvent are uniformly mixed to prepare a slurry, and the slurry is coated on nickel foam to obtain a loaded electrode sheet.
[0008] A standard three-electrode system was used, with a carbon rod as the counter electrode, a Hg / HgO electrode as the reference electrode, and nickel foam as the working electrode. The working electrode was pulsed activated in potassium hydroxide solution. During the activation process, Zn 2+ Ions are etched from the organic ligands on 2-methylimidazole to produce defective ZIF-8 pseudocapacitive materials. During pulse potential activation, the pulse intensity must be controlled, adjusted to the material's tolerance, to ensure vacancies are generated without damaging the material.
[0009] In a preferred embodiment of the present invention, during the pulse activation process, short pulses of cathode potential and short pulses of anode potential are repeated, with the cathode potential being -1.5V~-1.3V and the time being 1s~2s; the anode potential being 1.3V~1.5V and the time being 1s~2s, and repeating 150 times as one activation cycle.
[0010] The activation cycle is 3 to 5 times.
[0011] In a preferred embodiment of the present invention, the pyrolysis temperature is 350°C to 400°C.
[0012] In a preferred embodiment of the present invention, the pyrolysis time is 0.5 h and the heating rate is 5° C. / min.
[0013] In a preferred embodiment of the present invention, the mass ratio of ZIF-8 powder to acetylene black is 8:1.
[0014] The mass ratio of ZIF-8 powder to binder is 8:1.
[0015] The ratio of ZIF-8 powder to solvent was 8 mg:10 µL.
[0016] In a preferred embodiment of the present invention, the loading amount of the defective zeolite imidazolate framework material-8 on the loaded electrode sheet is 1 mg / cm 2 .
[0017] In a preferred embodiment of the present invention, the concentration of the potassium hydroxide solution is 1 mol / L.
[0018] The second object of the present invention is to provide a vacancy-type ZIF-8 pseudocapacitive material prepared by the above preparation method.
[0019] The third object of the present invention is to provide the application of the above-mentioned vacancy-type ZIF-8 pseudocapacitive material in pseudocapacitive supercapacitors.
[0020] Compared with the prior art, the present invention has the following beneficial effects: When the present invention prepares the defective ZIF-8 pseudocapacitive material, the synthesized ZIF-8 itself has a high specific surface area, and then is calcined in air to form N-doped porous carbon, which not only enhances the conductive activity, but also generates ZnO that provides the pseudocapacitive activity unique to metal oxides. Zn atoms are further etched from their intrinsic hexahedral organic framework by pulse activation, causing certain defects to the original 3D ordered pore structure without collapsing the hexahedral structure. This defective structure not only provides abundant active sites, but also significantly enhances the transfer efficiency of electrons, thereby improving the pseudocapacitive performance. Specifically, compared with the ZIF-8 material that has not been air-calcined and electrochemically etched, the defective ZIF-8 pseudocapacitive material prepared by the present invention increases the number of active sites and pseudocapacitive performance, thereby improving the charge transfer efficiency and increasing the Faraday reaction, i.e., the redox reaction, when the supercapacitor is working, which is reflected in the leap in the energy storage capacity of the supercapacitor.
[0021] The defective ZIF-8 material prepared by the preparation method of the present invention has excellent pseudocapacitive performance, exhibits high specific capacitance, has excellent energy density and power density, and can maintain good redox performance and energy storage capacity during long-term electrochemical reactions.
[0022] In addition, the preparation method of the present invention is simple to operate, has low requirements on equipment, and the operation process is highly controllable, which can further improve the output ratio of pseudocapacitive materials. It is very suitable for large-scale production and has important value. BRIEF DESCRIPTION OF THE DRAWINGS
[0023] Figure 1 This is a field emission scanning electron microscope image of ZIF-8 synthesized in step 1 of Example 1 of the present invention.
[0024] Figure 2This is a field emission scanning electron microscope image of ZIF-8 synthesized in step 1 of Example 2 of the present invention.
[0025] Figure 3 This is a field emission scanning electron microscope image of ZIF-8 synthesized in step 1 of Example 3 of the present invention.
[0026] Figure 4 This is a field emission scanning electron microscope image of defective ZIF-8 after electrochemical etching in Example 1 of the present invention.
[0027] Figure 5 1 is a Fourier transform infrared spectrum of the synthesized ZIF-8 in Example 1 of the present invention before and after calcination at 350° C. in air.
[0028] Figure 6 1 and 2 are cyclic voltammograms of the materials prepared in Example 1 and Comparative Examples 1 and 2 of the present invention.
[0029] Figure 7 1 and 2 are X-ray photoelectron spectra of the materials synthesized in Example 1 and Comparative Examples 1 and 2 of the present invention.
[0030] Figure 8 It is a specific surface area adsorption-desorption isotherm curve of ZIF-8 prepared in Comparative Example 1 of the present invention.
[0031] Figure 9 3 is a graph of the specific capacitance of the materials prepared in Example 1 and Comparative Examples 1 and 2 of the present invention. DETAILED DESCRIPTION
[0032] The following will clearly and completely describe the technical solutions in the embodiments of the present invention in conjunction with the accompanying drawings. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative efforts are within the scope of protection of the present invention.
[0033] The following experimental methods and detection methods, unless otherwise specified, are conventional methods; the following reagents and raw materials, unless otherwise specified, are commercially available reagents and raw materials. In addition, it should be noted that in the present invention, 2-methylimidazole is denoted as H-MIM, polyvinylidene fluoride is denoted as PVDF, and N-methylpyrrolidone is denoted as NMP.
[0034] Example 1 This embodiment provides a method for preparing a vacancy-type ZIF-8 pseudocapacitive material. The specific preparation steps are as follows: Step 1. Weigh 1.0864g of Zn(NO₃)₂·6H₂O and 17.0253g of H-MIM into beakers A and B, respectively, at a molar ratio of 1:56.85. Then, pour 36ml of methanol into beaker A containing the Zn(NO₃)₂·6H₂O, and 292.5ml of methanol into beaker B containing the H-MIM. Ultrasonicate each beaker for 10 minutes to fully dissolve and disperse the Zn(NO₃)₂·6H₂O. Then, transfer beaker B to a magnetic stirrer at 700 rpm, and slowly add the solution in beaker A dropwise to beaker B with stirring for 2 hours. The resulting milky white suspension is allowed to stand at room temperature for 22 hours to obtain a mixed solution. This is the Zn-2-methylimidazole complex.
[0035] After the reaction, the mixed solution was centrifuged and the solid was washed three times with methanol. This process required controlling the temperature of the mixed solution, specifically using an ice-water bath to maintain a stable temperature of 5°C to 10°C to facilitate successful product separation. The sediment was then collected and dried overnight in air at 60°C. After drying, the mixture was cooled naturally to room temperature, and the dried sample, ZIF-8, was removed.
[0036] Step 2: Grind the ZIF-8 obtained in step 1 in an agate grinding mortar for 15 minutes into powder and put it into a quartz boat. Then, place it in a tube furnace and pyrolyze it in an air atmosphere at a pyrolysis temperature of 350°C and a heating rate of 5°C min. -1 , the temperature was kept constant at 350℃ for 0.5 hours, and then the temperature was naturally lowered to obtain defective ZIF-8 powder, which was recorded as ZIF-8-350℃.
[0037] Step 3: According to the ratio of ZIF-8-350℃, acetylene black, PVDF and NMP of 8mg:1mg:1mg:10µL, 1mg ZIF-8-350℃, 0.125mg acetylene black, 0.125mg PVDF and 1.25µL NMP were taken in a centrifuge tube, ultrasonically dispersed for 1 hour, and then evenly applied to a 1×1cm 2 The loading amount of defective ZIF-8 active material on the nickel foam is about 1.0 mg cm -2 In this embodiment, the ZIF-8 loading amount on each electrode sheet is 1 mg, and the electrode sheet is kept at 60° C. and dried overnight under a vacuum environment to obtain an electrode sheet loaded with defective ZIF-8.
[0038] Step 4: A standard three-electrode system was used, with a carbon rod as the counter electrode, a Hg / HgO electrode as the reference electrode, and the electrode sheet prepared above as the working electrode. The defective ZIF-8 working electrode was pulsed activated in a 1M potassium hydroxide solution. The cathode potential was -1.5 V for 1 s, the anode potential was +1.5 V for 1 s, and the cathode potential short pulse was repeated 150 times followed by the anode potential short pulse. 150 repetitions constituted one activation cycle. The total time of one activation cycle was 300 s. In this embodiment, the activation cycle was 4 times, and the total holding time of oxidation activation and reduction activation was 1200 s. In this way, Zn 2+ Ions are etched from the organic ligands on 2-methylimidazole, further causing defects in the organic framework, and obtaining vacancy-type ZIF-8 electrode sheets, namely vacancy-type ZIF-8 pseudocapacitive materials, recorded as vacancy-type ZIF-8.
[0039] Example 2 This embodiment provides a method for preparing a vacancy-type ZIF-8 pseudocapacitive material. The specific preparation steps are as follows: Step 1. Weigh 1.0864g of Zn(NO₃)₂·6H₂O and 16.493g of H-MIM into beakers A and B, respectively, at a molar ratio of 1:55. Then, pour 35ml of methanol into beaker A containing the Zn(NO₃)₂·6H₂O, and 292ml of methanol into beaker B containing the H-MIM. Ultrasonicate each beaker for 10 minutes to fully dissolve and disperse the Zn(NO₃)₂·6H₂O. Then, transfer beaker B to a magnetic stirrer at 600 rpm, and slowly add the solution in beaker A dropwise to beaker B with stirring for 2 hours. The resulting milky white suspension is allowed to stand at room temperature for 23 hours to obtain a mixed solution. This is the Zn-2-methylimidazole complex.
[0040] After the reaction, the mixed solution was centrifuged and the solid was washed three times with methanol. This process required controlling the temperature of the mixed solution, specifically using an ice-water bath to maintain a stable temperature of 5°C to 10°C to facilitate successful product separation. The sediment was then collected and dried overnight in air at 60°C. After drying, the mixture was cooled naturally to room temperature, and the dried sample, ZIF-8, was removed.
[0041] Step 2: Grind the ZIF-8 obtained in step 1 in an agate grinding mortar for 15 minutes into powder and put it into a quartz boat. Then, place it in a tube furnace and pyrolyze it in air at a temperature of 400 °C and a heating rate of 5 °C min. -1 , kept constant temperature at 400℃ for 20min, and then cooled naturally to obtain defective ZIF-8 powder.
[0042] Step 3: According to the ratio of defective ZIF-8 powder, acetylene black, PVDF and NMP of 8mg:1mg:1mg:10µL, 1mg of defective ZIF-8 powder, 0.125mg of acetylene black, 0.125mg of PVDF and 1.25µL of NMP were taken in a centrifuge tube, and after being dispersed evenly by ultrasonication for 1 hour, the mixture was evenly applied on a 1×1cm 2 The loading amount of defective ZIF-8 active material on the nickel foam is about 1.0 mg cm -2 In this embodiment, the ZIF-8 loading amount on each electrode sheet is 1 mg, and the electrode sheet is kept at 60° C. and dried overnight under a vacuum environment to obtain an electrode sheet loaded with defective ZIF-8.
[0043] Step 4: A standard three-electrode system was used, with a carbon rod as the counter electrode, a Hg / HgO electrode as the reference electrode, and the electrode sheet prepared above as the working electrode. The defective ZIF-8 working electrode was pulsed activated in a 1M potassium hydroxide solution. The cathode potential was -1.3 V for 2 s, the anode potential was +1.3 V for 2 s, and the cathode potential short pulse was repeated 150 times followed by the anode potential short pulse. 150 repetitions constituted one activation cycle. The total time of one activation cycle was 600 s. In this embodiment, the activation cycle was 3 times, and the total holding time of oxidation activation and reduction activation was 1800 s. In this way, Zn 2+ Ions are etched from the organic ligands on 2-methylimidazole, further causing defects in the organic framework, and obtaining vacancy-type ZIF-8 electrode sheets, namely vacancy-type ZIF-8 pseudocapacitive materials.
[0044] Example 3 This embodiment provides a method for preparing a vacancy-type ZIF-8 pseudocapacitive material. The specific preparation steps are as follows: Step 1. Weigh 1.0864g of Zn(NO₃)₂·6H₂O and 17.0927g of H-MIM into beakers A and B, respectively, at a molar ratio of 1:57. Then, pour 37ml of methanol into beaker A containing the Zn(NO₃)₂·6H₂O, and 293ml of methanol into beaker B containing the H-MIM. Ultrasonicate each beaker for 10 minutes to fully dissolve and disperse the Zn(NO₃)₂·6H₂O. Then, transfer beaker B to a magnetic stirrer at 700 rpm, and slowly add the solution in beaker A dropwise to beaker B with stirring for 2 hours. The resulting milky white suspension is allowed to stand at room temperature for 24 hours to obtain a mixed solution. This is the Zn-2-methylimidazole complex.
[0045] After the reaction, the mixed solution was centrifuged and the solid was washed three times with methanol. This process required controlling the temperature of the mixed solution, specifically using an ice-water bath to maintain a stable temperature of 5°C to 10°C to facilitate successful product separation. The sediment was then collected and dried overnight in air at 60°C. After drying, the mixture was cooled naturally to room temperature, and the dried sample, ZIF-8, was removed.
[0046] Step 2: Grind the ZIF-8 obtained in step 1 in an agate grinding mortar for 15 minutes into powder and put it into a quartz boat. Then, place it in a tube furnace and pyrolyze it in an air atmosphere at a pyrolysis temperature of 360°C and a heating rate of 5°C min. -1 , maintained at a constant temperature of 360°C for 25 min, and then cooled naturally to obtain defective ZIF-8 powder.
[0047] Step 3: According to the ratio of defective ZIF-8 powder, acetylene black, PVDF and NMP of 8mg:1mg:1mg:10µL, 1mg of defective ZIF-8 powder, 0.125mg of acetylene black, 0.125mg of PVDF and 1.25µL of NMP were taken in a centrifuge tube, and after being dispersed evenly by ultrasonication for 1 hour, the mixture was evenly applied on a 1×1cm 2 The loading amount of defective ZIF-8 active material on the nickel foam is about 1.0 mg cm -2 In this embodiment, the ZIF-8 loading amount on each electrode sheet is 1 mg, and the electrode sheet is kept at 60° C. and dried overnight under a vacuum environment to obtain an electrode sheet loaded with defective ZIF-8.
[0048] Step 4: A standard three-electrode system was used, with a carbon rod as the counter electrode, a Hg / HgO electrode as the reference electrode, and the electrode sheet prepared above as the working electrode. The defective ZIF-8 working electrode was pulsed activated in a 1M potassium hydroxide solution. The cathode potential was -1.5 V for 1 s, the anode potential was +1.5 V for 1 s, and the cathode potential short pulse was repeated 150 times followed by the anode potential short pulse. 150 repetitions constituted one activation cycle. The total time of one activation cycle was 300 s. In this embodiment, the activation cycle was 5 times, and the total holding time of oxidation activation and reduction activation was 1500 s. In this way, Zn 2+ Ions are etched from the organic ligands on 2-methylimidazole, further causing defects in the organic framework, and obtaining vacancy-type ZIF-8 electrode sheets, namely vacancy-type ZIF-8 pseudocapacitive materials.
[0049] Comparative Example 1 This comparative example provides a method for preparing a ZIF-8 pseudocapacitive material. The specific preparation steps are as follows: Based on a molar ratio of Zn(NO₃)₂·6H₂O to H-MIM of 1:56.85, 1.0864g of Zn(NO₃)₂·6H₂O and 17.0253g of H-MIM were weighed into beakers A and B, respectively. 36ml of methanol was then poured into beaker A containing the Zn(NO₃)₂·6H₂O, and 292.5ml of methanol was poured into beaker B containing the H-MIM. Beakers A and B were each sonicated for 10 minutes to fully dissolve and disperse the Zn(NO₃)₂·6H₂O. Beaker B was then transferred to a magnetic stirring apparatus at 700 rpm, and the solution in beaker A was slowly added dropwise to beaker B with stirring for 2 hours. The resulting milky white suspension was allowed to stand at room temperature for 22 hours to obtain a mixed solution, which is the Zn-2-methylimidazole complex.
[0050] After the reaction, the mixed solution was centrifuged and the solid was washed three times with methanol. This process required controlling the temperature of the mixed solution, specifically using an ice-water bath to maintain a stable temperature of 5°C to 10°C to facilitate successful product separation. The sediment was then collected and dried overnight in air at 60°C. After drying, the mixture was cooled naturally to room temperature, and the dried sample, ZIF-8, was removed.
[0051] Comparative Example 2 This comparative example provides a method for preparing a defective ZIF-8 pseudocapacitive material. The specific preparation steps are as follows: Step 1. Weigh 1.0864g of Zn(NO₃)₂·6H₂O and 17.0253g of H-MIM into beakers A and B, respectively, at a molar ratio of 1:56.85. Then, pour 36ml of methanol into beaker A containing the Zn(NO₃)₂·6H₂O, and 292.5ml of methanol into beaker B containing the H-MIM. Ultrasonicate each beaker for 10 minutes to fully dissolve and disperse the Zn(NO₃)₂·6H₂O. Then, transfer beaker B to a magnetic stirrer at 700 rpm, and slowly add the solution in beaker A dropwise to beaker B with stirring for 2 hours. The resulting milky white suspension is allowed to stand at room temperature for 22 hours to obtain a mixed solution. This is the Zn-2-methylimidazole complex.
[0052] After the reaction, the mixed solution was centrifuged and the solid was washed three times with methanol. This process required controlling the temperature of the mixed solution, specifically using an ice-water bath to maintain a stable temperature of 5°C to 10°C to facilitate successful product separation. The sediment was then collected and dried overnight in air at 60°C. After drying, the mixture was cooled naturally to room temperature, and the dried sample, ZIF-8, was removed.
[0053] Step 2: Grind the ZIF-8 obtained in step 1 in an agate grinding mortar for 15 minutes into powder and place it in a quartz boat. Then place it in a tube furnace and complete pyrolysis in an air atmosphere. The pyrolysis temperature is 350°C and the heating rate is 5°C min -1 , the temperature was kept constant at 350℃ for 0.5 hours, and then the temperature was naturally lowered to obtain defective ZIF-8 powder, which was recorded as ZIF-8-350℃.
[0054] Step 3: According to the ratio of ZIF-8-350℃, acetylene black, PVDF and NMP of 8mg:1mg:1mg:10µL, 1mg ZIF-8 powder, 0.125mg acetylene black, 0.125mg PVDF and 1.25µL NMP were taken in a centrifuge tube, ultrasonically dispersed for 1 hour, and then evenly applied to a 1×1cm 2 The loading amount of defective ZIF active materials on the nickel foam is about 1.0 mg cm -2 , and kept dried at 60 °C under vacuum environment overnight to obtain an electrode sheet loaded with defective ZIF-8.
[0055] In order to characterize the vacancy-type ZIF-8 pseudocapacitive material prepared by the present invention, a standard three-electrode system was used, with a carbon rod as the counter electrode, a Hg / HgO electrode as the reference electrode, and the electrode sheets prepared in Example 1 and Comparative Example 2 as the working electrode. The performance test of the supercapacitor was carried out in an electrolyte of 3M potassium hydroxide solution. The test was performed using cyclic voltammetry, with the scanning potential between 1.1V and 1.5V relative to the standard hydrogen electrode to cover the entire redox active potential range of the material and ensure that all Faraday reactions were fully recorded, which was manifested as a complete redox peak in the cyclic voltammogram. The scanning rates were 5mV / s, 10mV / s, 15mV / s, and 20mV / s, respectively, to fully evaluate the performance of the material at different scan rates.
[0056] Figure 1 This is a field emission scanning electron microscope image of ZIF-8 synthesized in step 1 of Example 1 of the present invention. It can be seen that the product has a regular hexahedron morphology, and its average particle size is 30 nm through analysis.
[0057] Figure 2 This is a field emission scanning electron microscope image of ZIF-8 synthesized in step 1 of Example 2 of the present invention. By increasing the reaction time from 24 h to 25 h, the average particle size increases to 39 nm.
[0058] Figure 3 This is a field emission scanning electron microscope image of ZIF-8 synthesized in step 1 of Example 3 of the present invention. By increasing the reaction time from 24 h to 26 h, the average particle size increases to 52 nm.
[0059] Figure 4 This is a field emission scanning electron microscope image of the defective ZIF-8 after electrochemical etching in Example 1 of the present invention. It can be seen that the framework of the ZIF-8 is well preserved after electrochemical etching.
[0060] Figure 5 The Fourier transform infrared spectra of the synthesized ZIF-8 in Example 1 of the present invention before and after calcination in air at 350°C are shown. It can be seen that air calcination causes certain defects in ZIF-8, resulting in changes in the intensity of functional groups, such as 450cm -1 ~1500cm -1 The weakening of the C=C aromatic ring vibration between wavenumbers indicates that the imidazole ring is partially decomposed, 1700 cm -1 ~1750cm -1 The shoulder peak enhancement between wavenumbers is attributed to the formation of C=O bonds, indicating that the ligand is partially oxidized, which is beneficial to the hydrophilicity of the material and facilitates performance regulation. -1 ~600cm -1 A weak peak appears between the wavenumbers, which is attributed to the Zn-O vibration. ZnO begins to form on the surface, resulting in the exposure of Zn²⁺, forming unsaturated coordination sites and enhancing the pseudocapacitive activity.
[0061] After the ZIF-8 prepared in Comparative Example 1 and the defective ZIF-8 in Comparative Example 2 were made into electrode sheets, the supercapacitor performance of Example 1, Comparative Example 1 and Comparative Example 2 were tested respectively.
[0062] Figure 6 This is the cyclic voltammogram of the supercapacitor performance test of ZIF-8 prepared in Example 1 of the present invention, Comparative Example 1, and Comparative Example 2. It can be seen that after etching, the redox peak of ZIF-8 as a pseudocapacitive material has a certain shift, and the capacitance is greatly improved.
[0063] Figure 7 The X-ray photoelectron spectra of the products prepared in Example 1 and Comparative Examples 1 and 2 of the present invention show that Zn in ZIF-8 2+ It was successfully detached after electrochemical etching, the surface was successfully etched, and the defective ZIF-8 was successfully converted into vacancy-type ZIF-8.
[0064] Figure 8 This is the specific surface area adsorption-desorption isotherm curve of ZIF-8 prepared in comparative example 1 of the present invention. It can be seen that the ZIF-8 prepared in the present invention has an adsorption hysteresis loop, is a mesoporous material, and has a large specific surface area. It can provide more charge adsorption sites, accelerate ion transport, and is beneficial to subsequent etching.
[0065] Figure 9The cyclic voltammetry tests of the vacancy-type ZIF-8 prepared in Example 1 of the present invention, the ZIF-8 prepared in Comparative Example 1, and the defect-type ZIF-8 prepared in Comparative Example 2 obtained specific capacitances at different scan rates. It can be seen that after defects were introduced into ZIF-8 by air calcination and vacancies were produced by electrochemical etching, the specific capacitance gradually increased from tens of farads to 300 farads to 400 farads and then to 1500 farads to 2000 farads. It can be seen that the method proposed in the present invention has a good performance improvement on pseudocapacitive materials.
[0066] The synthesis method of the present invention can stably synthesize ZIF-8 with smaller particle size and higher specific surface area, with particle size less than 40nm and specific surface area greater than 1600m 2 / g, the capacitance performance is optimal.
[0067] In "The calcined zeolitic imidazolate framework-8 (ZIF-8) under different conditions as electrode for supercapacitor applications" published by GAO Y et al. in Journal of Solid State Electrochemistry, Vol. 18, No. 11, 2014, the specific capacitances of the original ZIF-8 and air-calcined ZIF-8 were 96 F / g and 156 F / g, respectively, which are lower than the specific capacitance of 300 F / g of the air-calcined ZIF-8 prepared in the present invention.
[0068] Compared with the prior art, the present invention improves the etching method for defective ZIF-8 pseudocapacitive materials. Unlike traditional etching methods that add chemicals, the present invention uses an electrochemical etching method, which is simple, increases production and saves energy. This method can effectively control the degree of defect etching in the ZIF-8 material, providing abundant active sites that facilitate electron transfer and improve the energy storage performance of ZIF-8 as a pseudocapacitive material. Furthermore, the material synthesis and etching methods are simple to operate, conveniently prepared, suitable for large-scale production, and have significant environmental and economic benefits. It can be widely used in the field of supercapacitors.
[0069] Although the preferred embodiments of the present invention have been described, those skilled in the art may make additional changes and modifications to these embodiments once they have learned the basic creative concept. Therefore, the appended claims are intended to be interpreted as including the preferred embodiments and all changes and modifications that fall within the scope of the present invention.
[0070] Obviously, those skilled in the art may make various modifications and variations to the present invention without departing from the spirit and scope of the present invention. Thus, if such modifications and variations fall within the scope of the claims and their equivalents, the present invention is intended to include such modifications and variations.
Claims
1. A method for preparing a vacancy-type ZIF-8 pseudocapacitive material, characterized in that: The following steps are involved: In an alcohol organic solvent, a zinc source and an imidazole organic ligand are added to cause a coordination reaction. During the reaction, the nitrogen of the imidazole organic ligand coordinates with the zinc ion in the zinc source to obtain a zeolite imidazole ester framework material-8; The zeolite imidazolate framework material-8 is pyrolyzed in an air atmosphere to obtain a defective zeolite imidazolate framework material-8; The defective zeolite imidazolate framework material-8, acetylene black, a binder and a solvent are uniformly mixed to prepare a slurry, and the slurry is coated on nickel foam to obtain a loaded electrode sheet; A standard three-electrode system was used, with a carbon rod as the counter electrode, a Hg / HgO electrode as the reference electrode, and nickel foam as the working electrode. The working electrode was pulsed activated in potassium hydroxide solution. During the activation process, Zn 2+ Ions are etched from the organic ligands on 2-methylimidazole to obtain defective ZIF-8 pseudocapacitive materials.
2. The method for preparing a vacancy-type ZIF-8 pseudocapacitive material according to claim 1, wherein: During the pulse activation process, short pulses of cathode potential and anode potential are repeated. The cathode potential is -1.5V~-1.3V, the time is 1s~2s; the anode potential is 1.3V~1.5V, the time is 1s~2s, and 150 repetitions constitute one activation cycle. The activation cycle is 3 to 5 times.
3. The method for preparing a vacancy-type ZIF-8 pseudocapacitive material according to claim 1, wherein: The pyrolysis temperature is 350℃~400℃.
4. The method for preparing a vacancy-type ZIF-8 pseudocapacitive material according to claim 1, wherein: The pyrolysis time was 0.5 h, and the heating rate was 5 °C / min.
5. The method for preparing a vacancy-type ZIF-8 pseudocapacitive material according to claim 1, wherein: The mass ratio of ZIF-8 powder and acetylene black is 8:1; The mass ratio of ZIF-8 powder and binder is 8:1; The ratio of ZIF-8 powder to solvent was 8 mg:10 µL.
6. The method for preparing a vacancy-type ZIF-8 pseudocapacitive material according to claim 1, wherein: The loading amount of defective zeolite imidazolate framework material-8 on the loaded electrode sheet is 1 mg / cm 2 .
7. The method for preparing a vacancy-type ZIF-8 pseudocapacitive material according to claim 1, wherein: The concentration of potassium hydroxide solution is 1 mol / L.
8. A vacancy-type ZIF-8 pseudocapacitive material prepared by the preparation method according to any one of claims 1 to 7.
9. Use of the vacancy-type ZIF-8 pseudocapacitive material according to claim 8 in a pseudocapacitive supercapacitor.
Citation Information
Patent Citations
Defect-state catalytic membrane derived from metal organic framework as well as preparation method and application of defect-state catalytic membrane
CN114768809A
Preparation method and application of ZIF-8 hierarchical porous material
CN115636950A
Preparation method of nickel-based self-supporting hydrogen evolution electrode
CN117187869A
Graphene and hydrotalcite composite material and preparation method thereof
CN120039871A
Electrodes having electrode additive for high performance batteries and applications of same
WO2020167725A1